High-temperature-resistant and high-strength concrete material for power plant and preparation method thereof
Through the use of specific formulas and processes in concrete materials, including the use of ball mill and power plant ash, the problem of concrete fluidity and water reduction in existing technologies has been solved, and high -strength and high temperature -resistant concrete materials are realized.
Patent Information
- Application Number
- CN202411575939.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
When existing concrete materials improve mechanical properties and high temperature resistance, the addition of inorganic reinforced materials leads to a decrease in rheology and water reduction, making it difficult to meet the needs of high strength and high temperature resistance.
A concrete material formula with high temperature resistance and high strength of power plants, including silicate cement, coarse materials, fine collection materials, high -efficiency water reducing agents, mineral mixes, composite external agents and high temperature resistant agents. The particle size distribution is distributed, and the ash is used as a mineral doping material to improve the strength and high temperature resistance of the concrete.
Realize the high strength and temperature resistance of concrete materials, improve the fluidity and water reduction, can effectively resist mechanical loads in high temperature environments, and extend the service life of concrete.
Smart Images

Figure BDA0005121794430000021 
Figure BDA0005121794430000031 
Figure BDA0005121794430000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a high-temperature resistant and high-strength concrete material for a power plant and a preparation method thereof. Background Art
[0002] With the development of modernization in my country, the forms of buildings have become more diverse. Many building forms such as large spans and high-rise buildings have increasingly put forward requirements on the strength of concrete. Concrete structures must be able to withstand various loads that may occur during the service life of the structure. In addition to their own gravity loads, they also include external loads such as static loads, dynamic loads and fire loads. In addition, under the high temperature of fire, the internal structure of concrete will undergo a series of physical and chemical changes, resulting in a sharp decline in the strength, stiffness and usability of the concrete, and ultimately leading to the failure of the concrete. Therefore, how to improve the strength and high temperature resistance of concrete is a technical problem that needs to be urgently solved in the preparation of modern concrete materials.
[0003] Patent application CN104030642A discloses a fiber concrete, including cement, fly ash, silica fume, aggregate, basalt fiber, polycarboxylate water-reducing agent and light silica fiber / crack-resistant fiber. The strength and other mechanical properties of the concrete are improved by adding inorganic fiber, and the durability of the concrete is improved by adding fly ash, silica fume and polycarboxylate water-reducing agent. However, the added silica fume and inorganic fiber will reduce the rheological properties of the concrete. In addition, it is also a technical problem that needs to be solved urgently to replace the existing inorganic fiber materials with a reasonably designed high-temperature resistant reinforcing agent to efficiently improve the waterproof performance and high-temperature resistance of the concrete.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a high-temperature resistant and high-strength concrete material for a power plant and a preparation method thereof, so as to solve the technical problem that when a certain amount of inorganic reinforcing material is added to the concrete material prepared in the prior art in order to improve its own mechanical properties and high-temperature resistance, its own rheology and water reduction properties are reduced.
[0006] The purpose of the present invention can be achieved by the following technical scheme: a high-temperature resistant and high-strength concrete material for a power plant, comprising, by weight, 10-15 parts of silicate cement, 45-55 parts of coarse aggregate, 5-10 parts of fine aggregate, 10-15 parts of water, 0.03-0.05 parts of high-efficiency water reducing agent, 1-5 parts of mineral admixture, 1-3 parts of composite admixture and 15-25 parts of high-temperature resistant reinforcing agent.
[0007] Furthermore, the preparation method of the composite admixture comprises the following steps:
[0008] B1, carboxymethyl starch and deionized water are mixed, heated and stirred to obtain a colorless, transparent, viscous solution, i.e., a starch solution; 0.1 mol / L NaOH solution is added dropwise to the starch solution to adjust the pH value of the starch solution to 8-9, and then alkalized at 55-65° C. for 1-2 h to obtain an alkalized starch solution;
[0009] B2, 2,3-epoxypropyltrimethylammonium chloride and deionized water are mixed and stirred to completely dissolve to obtain a quaternary ammonium salt aqueous solution; the quaternary ammonium salt aqueous solution is added dropwise to the alkalized starch solution, and after the addition is completed, the reaction is continued at 60-65° C. for 2-3 hours to obtain a reaction solution; the reaction solution is subjected to post-process treatment to obtain a quaternary ammonium salt modified starch;
[0010] Carboxymethyl starch and 2,3-epoxypropyltrimethylammonium chloride undergo a ring-opening reaction to prepare quaternary ammonium salt modified starch, and the reaction formula is as follows:
[0011]
[0012] B3, silicon tetrachloride and deionized water are mixed and stirred to obtain a polysilicic acid aqueous solution; then, quaternary ammonium salt-modified starch is added to the polysilicic acid aqueous solution, and stirred until the quaternary ammonium salt-modified starch is completely dissolved to obtain a composite admixture.
[0013] Silicon tetrachloride reacts with deionized water to obtain an aqueous polysilicic acid solution containing silicic acid, disilicate, trisilicic acid, etc. The aqueous polysilicic acid solution and quaternary ammonium salt modified starch can undergo a neutralization reaction to obtain a composite admixture.
[0014] Further, in step B1, the ratio of carboxymethyl starch to deionized water is 15-20g:100mL; in step B2, the ratio of 2,3-epoxypropyltrimethylammonium chloride to deionized water is 5-10g:30mL; the amount of quaternary ammonium salt aqueous solution added is 35-40mL; the post-process treatment includes: adding 0.1mol / L HCl solution dropwise to the reaction solution until the reaction solution is neutral, and then precipitating the reaction solution with anhydrous ethanol to obtain a solid; the solid is washed with deionized water and dried at 60°C to constant weight to obtain quaternary ammonium salt modified starch. In step B3, the ratio of silicon tetrachloride to deionized water is 5-25g:50mL.
[0015] Furthermore, the preparation method of the high-efficiency water reducing agent comprises the following steps:
[0016] A1, methacrylamide, allyl polyoxyethylene ether and deionized water are mixed, and then the temperature is raised to 60-90° C. to obtain a mixed monomer liquid;
[0017] A2. Add 10% wt ammonium persulfate aqueous solution dropwise to the mixed monomer liquid, and complete the addition within 1-2 hours. Then continue to keep warm at 60-90° C. for 3-6 hours, and then naturally cool to room temperature to obtain a reaction system; then adjust the pH value of the reaction system to 7-7.2 with 10-20% wt NaOH aqueous solution to obtain a high-efficiency water reducing agent.
[0018] Methacrylamide and allyl polyoxyethylene ether undergo addition reaction to obtain a high-efficiency water reducer, and the reaction formula is as follows:
[0019]
[0020] Furthermore, in step A1, the usage ratio of methacrylamide, allyl polyoxyethylene ether and deionized water is 8-15g:50-80g:200g, and the number average molecular weight of the allyl polyoxyethylene ether is 200; in step A2, the usage of the ammonium persulfate aqueous solution is 20-30mL.
[0021] Furthermore, the high temperature resistant enhancer is prepared by the following steps:
[0022] Expanded perlite and fly ash floating beads with an average particle size of 30-35 μm are mixed uniformly in a mass ratio of 1:1 to obtain component A; silicon nitride and boron nitride with an average particle size of 1-2 μm are mixed uniformly in a mass ratio of 1:1 to obtain component B; component A and component B are added to a high-speed airflow impact particle composite system in a mass ratio of 2-3:1 for composite treatment, the rotation speed of the high-speed airflow impact particle composite system is 3000-5000 r / min, the composite treatment time is 5-10 min, and a high temperature resistant enhancer is obtained.
[0023] The present invention also provides a method for preparing a high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0024] S1, coal gangue is selected and crushed by a crusher, then added to a ball mill for ball milling and sorting, and coal gangue with particle sizes of 4.75-9.5 mm and 9.5-19 mm are collected respectively to obtain coarse aggregate;
[0025] S2, basalt is selected from the raw materials, crushed by a crusher, and then added to a ball mill for ball milling and sorting, and basalt with particle sizes of 0.6-4.75mm and 0.075-0.6mm are collected respectively to obtain fine aggregate;
[0026] S3, adding water, high-efficiency water reducing agent and composite admixture into a mixing pot and stirring evenly, then adding cement into the mixing pot and mixing evenly to obtain cement slurry; adding coarse aggregate, fine aggregate, mineral admixture and high temperature resistant reinforcing agent into the above mixing pot, stirring at a low speed of 100-200r / min for 30s, then stirring at a high speed of 1000-2000r / min for 30s, then stopping stirring for 90s, and then stirring at a high speed of 1000-2000r / min for 60s to obtain concrete material;
[0027] S4, the concrete material is molded, demoulded, and then placed in a constant temperature water bath for curing to obtain a high-temperature resistant and high-strength concrete material for a power plant.
[0028] Furthermore, in step S3, the cement is P·II type silicate cement, the proportion of clinker and gypsum in the cement is 95-98%wt, and the proportion of granulated blast furnace slag is 2-5%wt.
[0029] Furthermore, in step S4, the curing humidity is ≥95%wt, the curing temperature is 18-22°C, and the curing age is 28d.
[0030] The present invention has the following beneficial effects:
[0031] 1. The concrete material prepared by the present invention includes silicate cement, coarse aggregate, fine aggregate, high-efficiency water reducing agent, mineral admixture, composite admixture, high temperature resistant reinforcing agent and water. In order to obtain good concrete workability, cement slurry not only needs to wrap the surface of aggregate particles, but also needs to fill the gaps between aggregate particles. Therefore, the ideal aggregate should have a smooth surface and particles that are approximately spherical. Therefore, the present invention collects coal gangue with particle sizes of 4.75-9.5mm and 9.5-19mm respectively through a ball milling process to obtain coarse aggregate; collects basalt with particle sizes of 0.6-4.75mm and 0.075-0.6mm respectively through a ball milling process to obtain fine aggregate; the gaps of large-particle coarse aggregate should be filled with fine aggregate, thereby reducing the amount of cement slurry required for concrete. In addition, the combination of aggregates of different particle sizes acts as a cement skeleton to adjust the density of concrete. The power plant ash produced after the combustion of the power plant contains a large amount of active silica and has a certain volcanic ash activity. By utilizing its volcanic ash properties and gelling properties, CSH gel is formed to improve interface defects and increase concrete strength. The application of power plant ash in concrete can not only solve the problem of power plant ash waste, but also reduce the amount of cement used and realize the comprehensive utilization of waste resources.
[0032] 2. In order to improve the high temperature resistance of the concrete material prepared by the present invention and to improve the strength of the concrete material, a certain amount of high temperature resistant reinforcing agent is added to the above concrete material. Expanded perlite contains phenocrysts, microcrystals and various forms of crystallites of sansitite and quartz, cryptocrystalline minerals; its porosity is very high, and it is a lightweight and efficient heat-insulating thermal insulation material. Fly ash floating beads are filled with nitrogen and carbon dioxide gases, and as glassy bead-shaped hollow microspheres, they can be used as thermal insulation materials. Silicon and nitrogen, nitrogen and boron in silicon nitride and boron nitride are bonded by strong covalent bonds, and are both high-temperature refractory compounds, and can be used as high temperature resistant materials. The above components are compounded to prepare a high temperature resistant reinforcing agent.
[0033] 3. A certain amount of high-efficiency water reducing agent and composite admixture are added to the concrete material of the present invention. In the composite admixture, the carboxylmethyl group in the carboxymethyl starch is a hydrophilic group. By introducing a very small amount of hydrophobic groups, a certain hydrophilic-lipophilic balance is achieved. The reversible three-dimensional network structure formed by physical chain entanglement, hydrophobic association, and hydrogen bonding in the aqueous solution makes the carboxymethyl starch have excellent thickening ability. The carboxymethyl starch is modified with 2,3-epoxypropyltrimethylammonium chloride and then reacted with a polysilicic acid aqueous solution to obtain a composite admixture. The modified starch can give the mortar special rheological properties and improve its solubility in cold water. In addition, the above-mentioned composite admixture can play a waterproof and hydrophobic role to a certain extent, can accelerate the cement hydration rate, increase the number of hydration products, and make the crystals finer. Polycarboxylic acid water reducer contains many hydrophilic groups such as hydroxyl, ether and carboxyl groups, so it has a certain liquid-gas interface activity. Therefore, the polycarboxylic acid water reducer has a certain air entrainment and slight slow setting properties. In order to further improve the water reducing performance of allyl polyoxyethylene ether, allyl polyoxyethylene ether is grafted with methacrylamide through addition reaction to further improve its own water absorption performance and obtain a high-efficiency water reducer. The concrete material prepared by the present invention has the advantages of high strength and high temperature resistance while having excellent rheology and water reducing properties. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing a composite admixture for high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0037] A1. Add 15g of carboxymethyl starch and 100mL of deionized water into a 100mL three-necked flask, heat the flask in a 70℃ oil bath, and stir at 300r / min until the solution becomes a colorless, transparent, viscous solution to obtain a starch solution. Add a certain amount of 0.1mol / L NaOH solution into the three-necked flask, adjust the pH value of the starch solution to 8, and then alkalize at 55℃ for 1h.
[0038] A2, 5g of 2,3-epoxypropyltrimethylammonium chloride and 30mL of deionized water were mixed and stirred and completely dissolved to obtain a quaternary ammonium salt aqueous solution. The above three-necked flask was equipped with a constant pressure separatory funnel, and 35mL of the quaternary ammonium salt aqueous solution was added dropwise to the three-necked flask through the separatory funnel. After the addition was completed, the oil bath was continued to heat at 60°C for 2h. After the reaction was completed, a reaction solution was obtained. 0.1mol / L HCl solution was then added dropwise to the reaction solution until the reaction solution was neutral, and the above reaction solution was precipitated with anhydrous ethanol to obtain a solid. The solid was washed with deionized water and dried at 60°C to constant weight to obtain a quaternary ammonium salt modified starch.
[0039] A3. Mix 5g of silicon tetrachloride and 50mL of deionized water into a 100mL beaker, stir at room temperature at 100r / min for 5min to obtain a polysilicic acid aqueous solution. Then add all of the quaternary ammonium salt modified starch into the polysilicic acid aqueous solution, stir until the quaternary ammonium salt modified starch is completely dissolved, and obtain a composite admixture.
[0040] Example 2
[0041] This embodiment provides a method for preparing a composite admixture for high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0042] A1. Add 18g of carboxymethyl starch and 100mL of deionized water into a 100mL three-necked flask, heat the flask in a 75℃ oil bath, and stir at 450r / min until the solution becomes a colorless, transparent, viscous solution to obtain a starch solution. Add a certain amount of 0.1mol / L NaOH solution into the three-necked flask, adjust the pH value of the starch solution to 8.5, and then alkalize at 60℃ for 1.5h.
[0043] A2, 6g of 2,3-epoxypropyltrimethylammonium chloride and 30mL of deionized water were mixed and stirred and completely dissolved to obtain a quaternary ammonium salt aqueous solution. The above three-necked flask was equipped with a constant pressure separatory funnel, and 38mL of the quaternary ammonium salt aqueous solution was added dropwise to the three-necked flask through the separatory funnel. After the addition was completed, the oil bath was continued to heat at 62°C for 2.5h. After the reaction was completed, a reaction solution was obtained. 0.1mol / L HCl solution was then added dropwise to the reaction solution until the reaction solution was neutral, and the above reaction solution was precipitated with anhydrous ethanol to obtain a solid. The solid was washed with deionized water and dried to constant weight at 60°C to obtain a quaternary ammonium salt modified starch.
[0044] A3. 15 g of silicon tetrachloride and 50 mL of deionized water were mixed and added to a 100 mL beaker, and the mixture was stirred at 120 r / min for 10 min at room temperature to obtain a polysilicic acid aqueous solution. The above quaternary ammonium salt modified starch was then added to the polysilicic acid aqueous solution, and stirred until the quaternary ammonium salt modified starch was completely dissolved to obtain a composite admixture.
[0045] Example 3
[0046] This embodiment provides a method for preparing a composite admixture for high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0047] A1. Add 20g of carboxymethyl starch and 100mL of deionized water into a 100mL three-necked flask, heat the flask in an 80℃ oil bath, and stir at 500r / min until the solution becomes a colorless, transparent, viscous solution to obtain a starch solution. Add a certain amount of 0.1mol / L NaOH solution into the three-necked flask, adjust the pH value of the starch solution to 9, and then alkalize at 65℃ for 2h.
[0048] A2, 10g of 2,3-epoxypropyltrimethylammonium chloride and 30mL of deionized water were mixed and stirred and completely dissolved to obtain a quaternary ammonium salt aqueous solution. The above three-necked flask was equipped with a constant pressure separatory funnel, and 40mL of the quaternary ammonium salt aqueous solution was added dropwise to the three-necked flask through the separatory funnel. After the addition was completed, the oil bath was continued to heat for 3h at 65°C. After the reaction was completed, a reaction solution was obtained. 0.1mol / L HCl solution was then added dropwise to the reaction solution until the reaction solution was neutral, and the above reaction solution was precipitated with anhydrous ethanol to obtain a solid. The solid was washed with deionized water and dried to constant weight at 60°C to obtain a quaternary ammonium salt modified starch.
[0049] A3. Mix 25g of silicon tetrachloride and 50mL of deionized water into a 100mL beaker, stir at 200r / min for 15min at room temperature to obtain a polysilicic acid aqueous solution. Then add all of the quaternary ammonium salt modified starch into the polysilicic acid aqueous solution, stir until the quaternary ammonium salt modified starch is completely dissolved, and obtain a composite admixture.
[0050] Example 4
[0051] This embodiment provides a method for preparing a high-efficiency water reducing agent for high-temperature resistant and high-strength concrete materials in a power plant, comprising the following steps:
[0052] B1. A 500 mL reactor was connected with a dropping funnel, a reflux condenser, a stirrer and a thermometer. Then 8 g of methacrylamide, 50 g of allyl polyoxyethylene ether and 200 g of deionized water were added to the reactor. The reactor was heated in an oil bath until the temperature reached 60°C to obtain a mixed monomer liquid.
[0053] B2, prepare 20mL of 10%wt ammonium persulfate aqueous solution; then add all the ammonium persulfate aqueous solution to the reactor through a dropping funnel, and complete the addition within 1 hour. Then place the reactor at 60°C for 3 hours of heat preservation, and then naturally cool to room temperature to obtain a reaction system. Then use 10%wt NaOH aqueous solution to adjust the pH value of the reaction system to 7 to obtain a high-efficiency water reducer.
[0054] Example 5
[0055] This embodiment provides a method for preparing a high-efficiency water reducing agent for high-temperature resistant and high-strength concrete materials in a power plant, comprising the following steps:
[0056] B1. A 500 mL reactor was connected with a dropping funnel, a reflux condenser, a stirrer and a thermometer. Then 10 g of methacrylamide, 60 g of allyl polyoxyethylene ether and 200 g of deionized water were added to the reactor. The reactor was heated in an oil bath until the temperature reached 80°C to obtain a mixed monomer liquid.
[0057] B2, prepare 25mL of 10%wt ammonium persulfate aqueous solution; then add all the ammonium persulfate aqueous solution to the reactor through a dropping funnel, and complete the addition within 1.2 hours. Then place the reactor at 80°C for 4 hours of heat preservation, and then naturally cool to room temperature to obtain a reaction system. Then use 15%wt NaOH aqueous solution to adjust the pH value of the reaction system to 7.1 to obtain a high-efficiency water reducer.
[0058] Example 6
[0059] This embodiment provides a method for preparing a high-efficiency water reducing agent for high-temperature resistant and high-strength concrete materials in a power plant, comprising the following steps:
[0060] B1. A 500 mL reactor was connected with a dropping funnel, a reflux condenser, a stirrer and a thermometer. Then 15 g of methacrylamide, 80 g of allyl polyoxyethylene ether and 200 g of deionized water were added to the reactor. The reactor was heated in an oil bath until the temperature reached 90°C to obtain a mixed monomer liquid.
[0061] B2, prepare 30mL of 10%wt ammonium persulfate aqueous solution; then add all the ammonium persulfate aqueous solution to the reactor through a dropping funnel, and complete the addition within 1 hour. Then place the reactor at 90°C for 3 hours of heat preservation, and then naturally cool to room temperature to obtain a reaction system. Then use 10%wt NaOH aqueous solution to adjust the pH value of the reaction system to 7.2 to obtain a high-efficiency water reducer.
[0062] Example 7
[0063] This embodiment provides a method for preparing a high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0064] S1. Expanded perlite and fly ash floating beads with an average particle size of 30 μm are mixed uniformly in a mass ratio of 1:1 to obtain component A. Silicon nitride and boron nitride with an average particle size of 1 μm are mixed uniformly in a mass ratio of 1:1 to obtain component B. Component A and component B are added to a high-speed airflow impact particle composite system in a mass ratio of 2:1 for composite treatment. The rotation speed of the high-speed airflow impact particle composite system is 3000 r / min, and the treatment time is 5 min to obtain a high temperature resistant enhancer.
[0065] S2. Collect the gangue discharged from the coal mine. After the material source is optimized, the gangue is crushed by a crusher, then added to a ball mill for ball milling and sorting. The gangue with particle sizes of 4.75-9.5mm and 9.5-19mm are collected to obtain coarse aggregate. Collect basalt. The basalt is crushed by a crusher, then added to a ball mill for ball milling and sorting. The basalt with particle sizes of 0.6-4.75mm and 0.075-0.6mm are collected to obtain fine aggregate.
[0066] S3. Add water, high-efficiency water reducing agent and composite admixture into the mixing pot, then add silicate cement into the mixing pot, the silicate cement is P·Ⅱ type silicate cement, the proportion of clinker and gypsum is 95%wt, the proportion of granulated blast furnace slag is 2%wt, mix evenly to obtain cement slurry. Add coarse aggregate, fine aggregate, mineral admixture power plant ash and high temperature resistant reinforcing agent into the above mixing pot, stir at a low speed of 100r / min for 30s, then stir at a high speed of 10000r / min for 30s, then stop stirring for 90s, and then stir at a high speed of 100r / min for 60s to obtain concrete material.
[0067] S4. The concrete material is molded, covered with a plastic film, demolded after 24 hours, and then placed in a constant temperature water bath for curing. The curing humidity is 95%wt, the curing temperature is 18°C, and the curing age is 28 days, thereby obtaining a high-temperature resistant and high-strength concrete material for a power plant.
[0068] Example 8
[0069] This embodiment provides a method for preparing a high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0070] S1. Expanded perlite and fly ash floating beads with an average particle size of 32 μm are mixed uniformly in a mass ratio of 1:1 to obtain component A. Silicon nitride and boron nitride with an average particle size of 1 μm are mixed uniformly in a mass ratio of 1:1 to obtain component B. Component A and component B are added to a high-speed airflow impact particle composite system in a mass ratio of 2:1 for composite treatment. The rotation speed of the high-speed airflow impact particle composite system is 4000 r / min, and the treatment time is 8 min to obtain a high temperature resistant enhancer.
[0071] S2. Collect the gangue discharged from the coal mine. After the material source is optimized, the gangue is crushed by a crusher, then added to a ball mill for ball milling and sorting. The gangue with particle sizes of 4.75-9.5mm and 9.5-19mm are collected to obtain coarse aggregate. Collect basalt. The basalt is crushed by a crusher, then added to a ball mill for ball milling and sorting. The basalt with particle sizes of 0.6-4.75mm and 0.075-0.6mm are collected to obtain fine aggregate.
[0072] S3. Add water, high-efficiency water reducing agent and composite admixture into the mixing pot, then add silicate cement into the mixing pot, the silicate cement is P·Ⅱ type silicate cement, the proportion of clinker and gypsum is 97%wt, the proportion of granulated blast furnace slag is 3%wt, mix evenly to obtain cement slurry. Add coarse aggregate, fine aggregate, mineral admixture power plant ash and high temperature resistant reinforcing agent into the above mixing pot, stir at a low speed of 150r / min for 30s, then stir at a high speed of 1500r / min for 30s, then stop stirring for 90s, and then stir at a high speed of 1500r / min for 60s to obtain concrete material.
[0073] Example 9
[0074] This embodiment provides a method for preparing a high-temperature resistant and high-strength concrete material for a power plant, comprising the following steps:
[0075] S1. Expanded perlite and fly ash floating beads with an average particle size of 35 μm are mixed uniformly in a mass ratio of 1:1 to obtain component A. Silicon nitride and boron nitride with an average particle size of 2 μm are mixed uniformly in a mass ratio of 1:1 to obtain component B. Component A and component B are added to a high-speed airflow impact particle composite system in a mass ratio of 3:1 for composite treatment. The rotation speed of the high-speed airflow impact particle composite system is 5000 r / min, and the treatment time is 10 min to obtain a high temperature resistant enhancer.
[0076] S2. Collect the gangue discharged from the coal mine. After the material source is optimized, the gangue is crushed by a crusher, then added to a ball mill for ball milling and sorting. The gangue with particle sizes of 4.75-9.5mm and 9.5-19mm are collected to obtain coarse aggregate. Collect basalt. The basalt is crushed by a crusher, then added to a ball mill for ball milling and sorting. The basalt with particle sizes of 0.6-4.75mm and 0.075-0.6mm are collected to obtain fine aggregate.
[0077] S3. Add water, high-efficiency water reducing agent and composite admixture into the mixing pot, then add silicate cement into the mixing pot, the silicate cement is P·Ⅱ type silicate cement, the proportion of clinker and gypsum is 98%wt, the proportion of granulated blast furnace slag is 5%wt, mix well to obtain cement slurry. Add coarse aggregate, fine aggregate, mineral admixture power plant ash and high temperature resistant reinforcing agent into the above mixing pot, stir at a low speed of 200r / min for 30s, then stir at a high speed of 2000r / min for 30s, then stop stirring for 90s, and then stir at a high speed of 2000r / min for 60s to obtain concrete material.
[0078] S4. The concrete material is molded, covered with a plastic film, demolded after 24 hours, and then placed in a constant temperature water bath for curing. The curing humidity is 98%wt, the curing temperature is 22°C, and the curing age is 28 days, thereby obtaining a high-temperature resistant and high-strength concrete material for a power plant.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 9 is that no composite admixture is added when preparing the concrete material.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 9 is that no high-efficiency water reducing agent is added when preparing the concrete material.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 9 is that no high temperature resistant reinforcing agent is added when preparing the concrete material.
[0085] Performance Testing:
[0086] 1. According to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the slump, expansion and setting time of the UHPC high temperature resistant and high strength concrete materials for power plants prepared in Examples 7-9 and Comparative Examples 1-3 were characterized.
[0087] 2. According to GBT31387-2015 "Reactive Powder Concrete", the compressive strength and flexural strength of the high-temperature resistant and high-strength concrete materials for power plants prepared in Examples 7-9 and Comparative Examples 1-3 were tested. The specific test results are shown in Table 1:
[0088] Table 1- Sample performance test data table
[0089]
[0090]
[0091] Data Analysis:
[0092] By comparing and analyzing the data in Table 1, a certain amount of composite admixtures was added to the high-temperature resistant and high-strength concrete materials for power plants prepared in Examples 7-9, thereby improving the fluidity of the prepared concrete materials, which is manifested in that the slump and expansion values of the prepared concrete materials are larger. However, in Comparative Example 1, no composite admixture was added to the prepared concrete materials, thereby reducing the fluidity of the prepared concrete materials, which is manifested in that the slump and expansion values are reduced.
[0093] A certain amount of high-efficiency water reducing agent was added to the high-temperature resistant and high-strength concrete materials for power plants prepared in Examples 7-9, thereby delaying the hydration process of cement and prolonging the setting time of concrete. However, in Comparative Example 2, no high-efficiency water reducing agent was added to the prepared concrete materials, thereby shortening the initial setting and final setting times.
[0094] A certain amount of high temperature resistant reinforcing agent was added to the high temperature resistant and high strength concrete materials for power plants prepared in Examples 7-9, thereby improving the mechanical properties thereof, which was manifested in an increase in the values of compressive strength and flexural strength. However, in Comparative Example 3, the high temperature resistant reinforcing agent was removed, thereby reducing the mechanical properties thereof, which was manifested in a decrease in the values of compressive strength and flexural strength.
[0095] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0096] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0097] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-temperature resistant and high-strength concrete material for a power plant, characterized in that: Calculated by weight, it includes 10-15 parts of Portland cement, 45-55 parts of coarse aggregate, 5-10 parts of fine aggregate, 10-15 parts of water, 0.03-0.05 parts of high-efficiency water reducing agent, 1-5 parts of mineral admixture, 1-3 parts of composite admixture and 15-25 parts of high temperature resistant reinforcing agent.
2. The high-temperature resistant and high-strength concrete material for power plants according to claim 1, characterized in that: The preparation method of the composite admixture comprises the following steps: B1, carboxymethyl starch and deionized water are mixed, heated and stirred to obtain a colorless, transparent, viscous solution, i.e., a starch solution; 0.1 mol / L NaOH solution is added dropwise to the starch solution to adjust the pH value of the starch solution to 8-9, and then alkalized at 55-65° C. for 1-2 h to obtain an alkalized starch solution; B2, 2,3-epoxypropyltrimethylammonium chloride and deionized water are mixed and stirred to completely dissolve to obtain a quaternary ammonium salt aqueous solution; the quaternary ammonium salt aqueous solution is added dropwise to the alkalized starch solution, and after the addition is completed, the reaction is continued at 60-65° C. for 2-3 hours to obtain a reaction solution; the reaction solution is subjected to post-process treatment to obtain a quaternary ammonium salt modified starch; B3, silicon tetrachloride and deionized water are mixed and stirred to obtain a polysilicic acid aqueous solution; then, quaternary ammonium salt-modified starch is added to the polysilicic acid aqueous solution, and stirred until the quaternary ammonium salt-modified starch is completely dissolved to obtain a composite admixture.
3. The high temperature resistant and high strength concrete material for power plants according to claim 2, characterized in that: In step B1, the dosage ratio of carboxymethyl starch to deionized water is 15-20 g:100 mL; in step B2, the dosage ratio of 2,3-epoxypropyltrimethylammonium chloride to deionized water is 5-10 g:30 mL; the dosage of the quaternary ammonium salt aqueous solution added is 35-40 mL; the post-process treatment comprises: adding 0.1 mol / L HCl solution dropwise to the reaction solution until the reaction solution is neutral, and then precipitating the reaction solution with anhydrous ethanol to obtain a solid; washing the solid with deionized water, and drying at 60° C. to constant weight to obtain quaternary ammonium salt modified starch; in step B3, the dosage ratio of silicon tetrachloride to deionized water is 5-25 g:50 mL.
4. The high-temperature resistant and high-strength concrete material for power plants according to claim 1, characterized in that: The preparation method of the high-efficiency water reducing agent comprises the following steps: A1, methacrylamide, allyl polyoxyethylene ether and deionized water are mixed, and then the temperature is raised to 60-90° C. to obtain a mixed monomer liquid; A2. Add 10% wt ammonium persulfate aqueous solution dropwise to the mixed monomer liquid, and complete the addition within 1-2 hours. Then continue to keep warm at 60-90° C. for 3-6 hours, and then naturally cool to room temperature to obtain a reaction system; then adjust the pH value of the reaction system to 7-7.2 with 10-20% wt NaOH aqueous solution to obtain a high-efficiency water reducing agent.
5. The high-temperature resistant and high-strength concrete material for power plants according to claim 4, characterized in that: In step A1, the usage ratio of methacrylamide, allyl polyoxyethylene ether and deionized water is 8-15g:50-80g:200g, and the number average molecular weight of the allyl polyoxyethylene ether is 200; in step A2, the usage amount of the ammonium persulfate aqueous solution is 20-30mL.
6. The high-temperature resistant and high-strength concrete material for power plants according to claim 1, characterized in that: The high temperature resistant enhancer is prepared by the following steps: Expanded perlite and fly ash beads with an average particle size of 30-35 μm are mixed uniformly in a mass ratio of 1:1 to obtain component A; silicon nitride and boron nitride with an average particle size of 1-2 μm are mixed uniformly in a mass ratio of 1:1 to obtain component B; component A and component B are added to a high-speed airflow impact particle composite system in a mass ratio of 2-3:1 for composite treatment, the rotation speed of the high-speed airflow impact particle composite system is 3000-5000 r / min, and the composite treatment time is 5-10 min to obtain a high temperature resistant enhancer.
7. A method for preparing a high-temperature resistant and high-strength concrete material for a power plant as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1, coal gangue is selected and crushed by a crusher, then added to a ball mill for ball milling and sorting, and coal gangue with particle sizes of 4.75-9.5 mm and 9.5-19 mm are collected respectively to obtain coarse aggregate; S2, basalt is selected and crushed by a crusher, then added to a ball mill for ball milling and sorting, and basalt with particle sizes of 0.6-4.75mm and 0.075-0.6mm are collected respectively to obtain fine aggregate; S3, adding water, high-efficiency water reducing agent and composite admixture into a mixing pot and stirring evenly, then adding cement into the mixing pot and mixing evenly to obtain cement slurry; adding coarse aggregate, fine aggregate, mineral admixture and high temperature resistant reinforcing agent into the above mixing pot, stirring at a low speed of 100-200r / min for 30s, then stirring at a high speed of 1000-2000r / min for 30s, then stopping stirring for 90s, and then stirring at a high speed of 1000-2000r / min for 60s to obtain concrete material; S4, the concrete material is molded, demoulded, and then placed in a constant temperature water bath for curing to obtain a high-temperature resistant and high-strength concrete material for a power plant.
8. The method for preparing a high-temperature resistant and high-strength concrete material for a power plant according to claim 7, characterized in that: In step S3, the cement is P·II type silicate cement, the proportion of clinker and gypsum in the cement is 95-98%wt, and the proportion of granulated blast furnace slag is 2-5%wt.
9. The method for preparing a high-temperature resistant and high-strength concrete material for a power plant according to claim 7, characterized in that: In step S4, the mineral admixture is power plant ash; the curing humidity is ≥95%wt, the curing temperature is 18-22°C, and the curing age is 28d.
Citation Information
Patent Citations
Fiber concrete
CN104030642A